DNA sequence and community structure diversity of multi-year soil fungi in Grape of Xinjiang - Feng Xue (Nature Portfolio, 2021)
Abstract This study is designed to understand the community structure and diversity of fungi in the rhizosphere soil of grape. As the sample for this study, the rhizosphere soil of Crimson seedless grape with different planting years was collected from Shihezi in Xinjiang to carry out high-throughput sequencing, by which the complete sequence of soil fungi DNA was identified, and accordingly, the richness and diversity index of fungi were determined. The results showed that the dominant phyla of fungi in the grape rhizosphere soil with different planting years were Ascomycota and Basidiomycota, and the dominant classes of fungi were Sordariomycetes and Dothideomycetes. Soil organic matter, total potassium, total nitrogen and available phosphorus were the main soil fertility factors affecting the abundance and diversity of soil fungal communities, among which soil organic matter had the most significant influence. In addition, the fungal diversity and richness were highest in the middle layer (20–35 cm) of the grape rhizosphere soil with 12 planting years and lowest in the lower layer (35–50 cm) of the grape rhizosphere soil with 5 planting years. Linear discriminant analysis suggested that there were more biomarkers in the vineyard rhizosphere soil with 10 planting years, which meant there were more fungal communities with significant difference in the soil, especially in the middle layer (20–35). The results of this study can provide data reference and theoretical basis for improving vineyard soil quality, evaluating soil microecological effects and improving ecological environment of vineyard soil.